2008
DOI: 10.1021/jf0732408
|View full text |Cite
|
Sign up to set email alerts
|

Human Exposure to Perfluorinated Chemicals through the Diet: Intake of Perfluorinated Compounds in Foods from the Catalan (Spain) Market

Abstract: The aim of this study was to determine the dietary intake of perfluorinated chemicals (PFCs) by the population of Tarragona County (Catalonia, Spain). PFC levels were determined in 36 composite samples of foodstuffs randomly purchased in various locations. Exposure to PFCs through the diet was estimated for various age/gender groups. Perfluorooctane sulfonate (PFOS), perfluorocarboxylate perfluorooctanoate (PFOA), and perfluoroheptanoic acid (PFHpA) were the only detected PFCs in foodstuffs. On average, for a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

27
204
10
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 258 publications
(243 citation statements)
references
References 31 publications
27
204
10
2
Order By: Relevance
“…A recent survey on the human exposure to PFCs through the diet carried out in Spain suggested that fish was the main contributor to PFOS in human beings. 7 In this work, risk assessment based on dietary intake of mollusks for the local residents was conducted on the basis of the study by Gulkowsaka et al 18 Since investigations on the daily consumption of related mollusks was not conducted in the sampling locations, data collected in Zhoushan, which is also a coastal city, was adopted for reference in the present study. 18 The daily consumption (g per person, wet weight) of bivalves (mussels, oysters, and clams) was estimated to be 76 g for the Zhoushan population (1172 g total intake/day).…”
Section: Discussionmentioning
confidence: 99%
“…A recent survey on the human exposure to PFCs through the diet carried out in Spain suggested that fish was the main contributor to PFOS in human beings. 7 In this work, risk assessment based on dietary intake of mollusks for the local residents was conducted on the basis of the study by Gulkowsaka et al 18 Since investigations on the daily consumption of related mollusks was not conducted in the sampling locations, data collected in Zhoushan, which is also a coastal city, was adopted for reference in the present study. 18 The daily consumption (g per person, wet weight) of bivalves (mussels, oysters, and clams) was estimated to be 76 g for the Zhoushan population (1172 g total intake/day).…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have investigated the determinants of dietary intake or blood levels of PFOS in Japan. However, market basket studies have shown that dietary intake of PFOS derived mainly from fish and seafood in Spain 10) , and cereals and cereal products, milk and dairy products, fish and seafood, and meat and meat products in Norway 2) . Two previous reports also reported that consumption of fish and shellfish was positively correlated with plasma or serum concentrations of PFOS in Norway 9,31) .…”
Section: Discussionmentioning
confidence: 99%
“…However, there is still debate over the sources of dietary exposure to PFOS and PFOA in humans. Several reports have indicated that PFOS and PFOA were transferred into the human body mainly through fish intake 9,10) . On the other hand, research in Denmark showed positive associations between concentrations of PFOS in blood and consumption of red meat, animal fat and snacks, but not fish 11) .…”
mentioning
confidence: 99%
“…As demonstrated previously, food consumption, especially fish consumption is a major pathway for human exposure to PFASs (Falandysz et al, 2006;Ericson et al, 2008;Fromme et al, 2009;Berger et Assuming an average human body weight of 60 kg and muscle being the only consumed tissue, the amount of fish consumption is about 60 kg per person per year in Hong Kong (Dickman and Leung, 1998). Taking geographical location and eating habits of life into account, the same fish consumption rate was used for the calculation in this region.…”
Section: Risk Assessment Through Fish Consumptionmentioning
confidence: 99%